2021
DOI: 10.3390/foods10102329
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Chewing Candy Formulations Based on Acetic, Alcoholic, and Lactofermented Apple Juice Products

Abstract: The aim of this study was to develop nutraceutical chewing candy (NCC) formulations based on acetic, alcoholic, and lactofermented apple juice (AJ) products. In addition, different texture-forming (gelatin, pectin) and sweetening (stevia, xylitol) agents were tested. To implement the aim of this study, combinations based on AJ, prepared from fresh and frozen apples, apple cider (C) samples (No.1, No.2, No.3, and No.4), and apple vinegar (V) were used. First, the most appropriate combination was selected by eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For instance, LAB can excrete or produce bioactive compounds, such as bacteriocins, organic acids, and hydrogen peroxide, which inhibit the growth of other bacteria, yeast, and moulds [ 125 , 126 , 127 ]. Furthermore, plant ingredients, such as blackcurrants [ 32 , 36 , 46 ], apples [ 32 , 49 , 128 ], raspberries [ 36 , 37 ], rowanberries [ 32 , 129 ], and cranberries [ 130 , 131 ], also exert inhibitory effects on undesirable bacteria growth. Our findings agreed with those of Klupsaite et al [ 19 ], who found that treating LM with lactobacilli in combination with other plant-based ingredients (i.e., Thymus vulgaris essential oil) can improve the safety parameters of the meat.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, LAB can excrete or produce bioactive compounds, such as bacteriocins, organic acids, and hydrogen peroxide, which inhibit the growth of other bacteria, yeast, and moulds [ 125 , 126 , 127 ]. Furthermore, plant ingredients, such as blackcurrants [ 32 , 36 , 46 ], apples [ 32 , 49 , 128 ], raspberries [ 36 , 37 ], rowanberries [ 32 , 129 ], and cranberries [ 130 , 131 ], also exert inhibitory effects on undesirable bacteria growth. Our findings agreed with those of Klupsaite et al [ 19 ], who found that treating LM with lactobacilli in combination with other plant-based ingredients (i.e., Thymus vulgaris essential oil) can improve the safety parameters of the meat.…”
Section: Resultsmentioning
confidence: 99%
“…Kavvadias et al [61] have reported additional dioxanes in apple wine, presumably deriving from the reaction of aldehydes other than acetaldehyde with the aforementioned 1,3diols such as propanal, butanal, 2-methylpropanal, hexanal, 3-methylbutanal, and 2-methylbutanal as well as the ketones acetone and 2-butanone. In particular, cyclic 1,3-dioxanes have been reported to contribute to cider aroma [10,65]. The conversion of unpleasant aldehydes and ketones into dioxanes may have a positive impact on aroma, as the dioxanes exert a weak but pleasant "green note" flavor [61].…”
Section: Supervised Discrimination By Pls-damentioning
confidence: 99%
“…Like cider, the brewing of beer is an ancient process dating as far back as 8000 years. However, it is only technological advancements over the past 150 years or so that brings us to a modernized practice of several methods of brewing we are now familiar with (Bamforth, 2002), resulting in many unique types of beer such as ale, stout, and lager, which are the most popular and common types of beer brewed worldwide. The ingredients in beer are often altered to produce unique properties and characteristics in specific types (Nogueira et al, 2017).…”
Section: Beer Productionmentioning
confidence: 99%
“…2004;Tolstrup & Grønbaek, 2007). Other beneficial health properties can be attributed to the hop and cereal-related compounds that are free of sugar, cholesterol, or fat, the inclusion of phenolic compounds with strong antioxidant and anti-inflammatory properties, soluble fiber, magnesium, and other micronutrients (Bamforth, 2002).…”
Section: Beer Productionmentioning
confidence: 99%
See 1 more Smart Citation